The effect of polypharmacy on rheumatoid and psoriatic arthritis treatment: retrospective study - Kara, Mete; Alp, Gülay; Palanbek Yavaş, Seher; Taşdemir, Anıl; Ketenci, Sertaç; Kara, Müge Mercan; Ozduran, Erkan (PeerJ, 2023)
Background Rheumatoid arthritis (RA) and psoriatic arthritis (PsA) are chronic, progressive inflammatory diseases that can be accompanied by other diseases. In recent years, with the increase in the lifespan of individuals, the concept of polypharmacy has become more prominent. We aimed to show the prevalence of polypharmacy and the effects of polypharmacy on disease activity in RA and PsA. Methods This study included PsA patients who had peripheral joint involvement and, RA patients. Since PsA has a heterogeneous clinical picture, only patients with peripheral joint involvement were included in the study and patients with inflammatory low back pain or radiological sacroiliitis or spondylitis, dactylitis or enthesitis were not included in the study due to homogeneity concerns. The numbers of medications used by the patients at the onset of their treatment and at sixth months into their treatment were recorded. Polypharmacy was accepted as the simultaneous use of at least five medications by the person. The Disease Activity Score 28 joints C-Reactive Protein (DAS-28 CRP) was used to assess disease activity for both disease. The modified Charlson Comorbidity Index (CCI) scores of the patients were calculated based on their chronic diseases. Results The sample of the study included 232 RA and 73 PsA patients. Polypharmacy was present at the treatment onset in 115 (49.6%) of the RA patients and 28 (38.4%) of the PsA patients. At the sixth month of treatment, polypharmacy was present in the sixth month of the treatment in 217 (93.5%) RA and 61 (83.6%) PsA patients. The mean ages of the RA and PsA patients who were receiving polypharmacy treatment at the beginning were significantly older than the mean ages of those who were not receiving polypharmacy treatment. In both the RA and PSA groups, the patients with polypharmacy at the beginning had statistically significantly higher DAS-28 CRP scores at six months of treatment than those without polypharmacy at the beginning (p < 0.001). Conclusion Polypharmacy was present both at the time of diagnosis and in the treatment process in the RA and PsA patients, and the presence of polypharmacy at the beginning of the treatment was among the factors that affected the treatment of these patients by significantly affecting their 6th-month DAS-28 CRP values.
Keywords: Polypharmacy; Rheumatoid arthritis; Psoriatic arthritis; DAS-28; DMARD